Effect of particle size and filler type in polymeric material insulations - Wan Mohd Zawawi, Wan Akmal Izzati (2012)
Electrical equipments mainly use polymeric material as insulation due to its characteristic of having high resistance to repel/retard electrical discharge attack, thermal conductivity, tree growth, and chemical cavities. Recently, polymer composite has been modified with addition of nano-sized filler instead of the conventional micro-sized filler. It was found that addition of nano-sized filler in polymer composite provides better characteristic if they are prepared and fabricated properly. The interfaces of the filler plays role in determining the behaviour of the polymeric insulation. Addition of different types of filler i.e. silica (SiO2), titania (TiO2), alumina (Al2O3), zinc oxide (ZnO), magnesium oxide (MgO), clay, etc. also gives different dielectric behaviour to polymeric insulation. This paper provides a review on the effect of particle size and types of filler on polymeric material insulation. In attempt to identify the characteristic of these fillers on polymeric insulation, partial discharge (PD) amplitude, erosion depth, breakdown strength, glass transition temperature, and scanning electron microscopy (SEM) images of polymer composite samples are studied. The role of interfaces is also explained.